ANALISIS BENTUK DAN PENGGUNAAN ONOMATOPE PADA ANIME HETALIA: WORLD STARS - Nurazizah, Erin; Fitriana, Ita; Yasmin Adellia Putri Fe (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Language serves as an agreed-upon symbol of sound used by humans for communication among groups. Each language has its unique characteristics, including onomatopes, which are words that describe sounds or conditions. Japanese is rich with onomatopes, categorized mainly into two types: gion-go (sounds from inanimate objects and nature) and gisei-go (sounds from living beings). Additionally, there exists gitai-go to describe silent states. In the context of the anime "Hetalia: World Stars," these onomatopes enhance dialogue and add comedic elements, creating humorous interactions between characters representing nations with specific traits and stereotypes. This study aims to identify and analyze the types and meanings of onomatopes within this anime using qualitative descriptive methods. The collected data through observation and note-taking resulted in 55 identified onomatopes across 15 episodes, consisting of 16 gion-go, 14 gisei-go, 7 gitai-go, 12 giyou-go, and 6 gijou-go. Findings indicate that the use of onomatopes not only functions aesthetically but also strengthens emotions and character development in the narrative. This research hopes to provide deeper insights into the varieties of onomatopes in Japanese alongside practical implications for the animation industry. Keywords: onomatopes, hetalia, japanese language.